State of disarray : public policy in the Caribbean. - THOMAS, Clive Y. (1996)
Analyses the role of the United Nations in promoting, guaranteeing and defending human rights, with particular emphasis on the Convention on the Rights of the Child. Points out that most of the countries in the world have now ratified the Convention, and the real challenge is how to progress from massive ratification to massive implementation.